2013
DOI: 10.1371/journal.pone.0073814
|View full text |Cite
|
Sign up to set email alerts
|

Altered Metabolites in the Plasma of Autism Spectrum Disorder: A Capillary Electrophoresis Time-of-Flight Mass Spectroscopy Study

Abstract: Clinical diagnosis and severity of autism spectrum disorders (ASD) are determined by trained clinicians based on clinical evaluations of observed behaviors. As such, this approach is inevitably dependent on the expertise and subjective assessment of those administering the clinical evaluations. There is a need to identify objective biological markers associated with diagnosis or clinical severity of the disorder. To identify novel candidate metabolites as potential biomarkers for ASD, the current study applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 53 publications
4
51
0
1
Order By: Relevance
“…Emond and colleagues, 27 using a gas chromatography-mass spectroscopy (GC-MS)-based approach in an analysis of urine samples, built a multivariate statistical model that captured global biochemical signatures of autistic individuals, which enabled them to be distinguished very well from healthy children. Kuwabara and colleagues, 28 using capillary electrophoresis time-of-flight mass spectroscopy (CE-TOF MS) for high-throughput profiling of metabolite levels in plasma, identified deviated levels of plasma metabolites associated with oxidative stress and mito chondrial dysfunction in individuals with ASD.…”
Section: J Psychiatry Neurosci 2016;41(1)mentioning
confidence: 99%
“…Emond and colleagues, 27 using a gas chromatography-mass spectroscopy (GC-MS)-based approach in an analysis of urine samples, built a multivariate statistical model that captured global biochemical signatures of autistic individuals, which enabled them to be distinguished very well from healthy children. Kuwabara and colleagues, 28 using capillary electrophoresis time-of-flight mass spectroscopy (CE-TOF MS) for high-throughput profiling of metabolite levels in plasma, identified deviated levels of plasma metabolites associated with oxidative stress and mito chondrial dysfunction in individuals with ASD.…”
Section: J Psychiatry Neurosci 2016;41(1)mentioning
confidence: 99%
“…Arginine has been described to be higher in plasma samples of ASD children. 40 Excessive arginine is thought to induce oxidative stress via NO production. 41 We also found perturbations of guanidinosuccinic acid and methylguanidine, which are produced from oxidation of argininosuccinic acid and creatine, respectively, by free radicals.…”
Section: C18 Analysismentioning
confidence: 99%
“…Grioli et al (6) reported that 5-oxoproline was effective in improving some verbal memory functions in subjects affected by age-related memory decline. A recent study has shown that 5-oxoproline could become a possible biomarker for autism spectrum disorders (7).…”
mentioning
confidence: 99%